2013
DOI: 10.1370/afm.1488
|View full text |Cite
|
Sign up to set email alerts
|

Recognition as a Patient-Centered Medical Home: Fundamental or Incidental?

Abstract: PURPOSELittle is known about reasons why a medical group would seek recognition as a patient-centered medical home (PCMH). We examined the motivations for seeking recognition in one group and assessed why the group allowed recognition to lapse 3 years later.METHODS As part of a larger mixed methods case study, we conducted 38 key informant interviews with executives, clinicians, and front-line staff. Interviews were conducted according to a guide that evolved during the project and were audiorecorded and fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11] Facilitators and barriers to the creation of a successful PCMH have been explored in a limited number of heterogeneous settings, including small practices, large group practices, high-performing practices, and safety net clinics. [12][13][14][15][16][17] To date, significant challenges have been identified; specifically, the investment of resources for infrastructure changes and the leadership skills needed to guide an organization through paradigm-shifting cultural change. 5,14,18 Common facilitators have included valuing innovation, quality improvement, and patient-centeredness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11] Facilitators and barriers to the creation of a successful PCMH have been explored in a limited number of heterogeneous settings, including small practices, large group practices, high-performing practices, and safety net clinics. [12][13][14][15][16][17] To date, significant challenges have been identified; specifically, the investment of resources for infrastructure changes and the leadership skills needed to guide an organization through paradigm-shifting cultural change. 5,14,18 Common facilitators have included valuing innovation, quality improvement, and patient-centeredness.…”
Section: Introductionmentioning
confidence: 99%
“…5,14,18 Common facilitators have included valuing innovation, quality improvement, and patient-centeredness. 12,13,16 We sought to augment the literature on motivations, barriers, and facilitators to PCMH implementation by describing a large-scale initiative with some unique features.…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous research has shown that the decision to pursue NCQA PCMH recognition often is based on financial incentives. 2,3 In addition, the desire to become a patient-centered practice and to seek NCQA recognition are not necessarily aligned: "PCMH recognition per se at times amounts to a small incentive to change labels." 2 True transformation to a PCMH requires a dramatic shift in practice culture and mental models.…”
mentioning
confidence: 99%
“…2,3 In addition, the desire to become a patient-centered practice and to seek NCQA recognition are not necessarily aligned: "PCMH recognition per se at times amounts to a small incentive to change labels." 2 True transformation to a PCMH requires a dramatic shift in practice culture and mental models. 4 As part of a study of primary care workforce innovations funded by The Robert Wood Johnson Foundation, we consulted with 387 national experts in primary care research, using both purposeful and snowball sampling, to identify a set of 131 practices that experts knew to be (1) high quality, (2) clinically excellent settings, and (3) doing something innovative with their staffing (Table 1).…”
mentioning
confidence: 99%
“…2 Payers would want to know whether the money is best spent on supporting PCMH at a certain level or on paying for team care directly. At present, this study provides valuable lessons from the frontline on how successful PCMHs have overcome challenges to successfully develop and sustain a teamwork approach.…”
mentioning
confidence: 99%